2015
DOI: 10.1371/journal.pone.0137080
|View full text |Cite|
|
Sign up to set email alerts
|

Validation of the FEEL-KJ: An Instrument to Measure Emotion Regulation Strategies in Children and Adolescents

Abstract: Although the field of emotion regulation in children and adolescents is growing, there is need for age-adjusted measures that assess a large variety of strategies. An interesting instrument in this respect is the FEEL-KJ because it measures 7 adaptive and 5 maladaptive emotion regulation strategies in response to three different emotions. However, the FEEL-KJ has not yet been validated extensively. Therefore, the current study aims to test the internal structure and validity of the FEEL-KJ in a large sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
72
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 37 publications
2
72
0
1
Order By: Relevance
“…QoL post‐gonadotropin treatment, compared to pretreatment, assessed by three standardized questionnaires: ‘Inventory for assessment of quality of life in children and adolescents’ (‘ILK’), ‘Inventory for assessment of depression in children and adolescents’ (‘DIKJ’) and ‘Questionnaire for assessment of emotion regulation strategies in children and adolescents’ (‘FEEL‐KJ’), and by two questions on self‐perceived satisfaction with testis size and masculinity.…”
Section: Methodsmentioning
confidence: 99%
“…QoL post‐gonadotropin treatment, compared to pretreatment, assessed by three standardized questionnaires: ‘Inventory for assessment of quality of life in children and adolescents’ (‘ILK’), ‘Inventory for assessment of depression in children and adolescents’ (‘DIKJ’) and ‘Questionnaire for assessment of emotion regulation strategies in children and adolescents’ (‘FEEL‐KJ’), and by two questions on self‐perceived satisfaction with testis size and masculinity.…”
Section: Methodsmentioning
confidence: 99%
“…Items are answered on a five-point Likert scale (from 0= not at all to 4= almost always). For the Dutch and Flemish population, representative norms are available (Braet et al, 2013) and a good reliability and validity was found (Cracco, van Durme, & Braet, 2015).…”
Section: Fragebogen Zur Erhebung Der Emotionsregulation Bei Kindern Umentioning
confidence: 99%
“…Each strategy is measured by rating two items for each of the three emotions, whereby answers are given on a 5-point Likert scale (1 = almost never; 2 = rarely; 3 = occasionally; 4 = often; 5 = almost always). Regarding psychometric qualities, the FEEL-KJ is well-validated and reliable (Cracco, Van Durme, & Braet, 2015). As the current study aims to include a broad range of adaptive emotion regulation strategies, a global composite score of teacher-rated adaptive emotion regulation was used (42 items; α = .97).…”
Section: Emotion Regulation Strategiesmentioning
confidence: 99%